PENGARUH BOOK TAX DIFFERENCES TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR KEUANGAN - Darma, Elisa Gunawan; Hastuti, Rini Tri (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to examine the effect of Book Tax Difference which has been caused by temporary differences and permanent differences in profit growth in financial sector companies listed on the Indonesia Stock Exchange BEI in 2019-2022. The selection of the sample that the author uses is based on purposive sampling with certain criteria and uses secondary data in the form of financial reports obtained from the sites www.idx.co.id, www.sahamee.com, www.britama.com. This study used a sample of 31 companies (banks and insurance companies). Data management techniques using Eviews 12 and Microsoft Excel. Based on the results of research that has been done by the author, it can be concluded that in this study it shows that Temporary Differences in Book Tax Differences have no effect on profit growth and permanent differences in Book Tax Differences have no effect on profit growth.